Função social da propriedade: os instrumentos legais para sua execução no meio urbano - Souza, Ada Celi Rezende (2017)
The objective of this research was to investigate the social function of the property in the urban perimeter, considering the analysis of the current property conception in the Brazilian context and the identification of the legal instruments that corrobor ate the execution of its social function in the Lavras city, through a case study. It was a qualitative and descriptive type research, using documents of primary and secondary sources. Through the information assessment, it was verified that the social fun ction of the urban property in the Brazilian context, although it has gotten important interest in the last decades, with its inclusion in the 1988 Brazilian Constitution and subsequent regulation by the Statute of the City, in 2001, and both of them just happened under strong pressure of the popular movements, it is still notable the predominance of an individualistic and absolute conception of property, considered its foundations on the economy. This persistence is translated as resistance to legal determinations or even the connivance of the State itself with excluding real estate markets, creating conflicting situations with the social interests. Regarding the delegation for the responsibility to the municipal districts, by the 1988 Brazilian Constitutio n, to effective the social function of the property in the urban space, authors‟ opinion divergences point out positive and negative aspects as the direct contact of the municipal public entities with the social reality of its own city, but also the larger consent from these entities to the illegal production of the urban space, respectively. In the case of Lavras, the situation does not differ from the Brazilian general context. Despite having several legal instruments foreseen in the city planning, to execute the social function of the property in the urban environment, as laws of subdivision, zoning, land use and occupation, as well as compulsory use, with the establishment of progressive IPTU taxes; there is a difficulty in applying them. Moreover, it wa s highlighted the creation of laws that are not effective in achieving the social function of property, what demonstrates indifference from the public power in executing it, because not rarely the public power is hostage of the real estate market. Finally, it was emphasized the importance of the participation of society in the whole process of creating these instruments for the defense of collective rights, from its elaboration until it is fully implemented.